2013
DOI: 10.4236/sn.2013.21001
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Use of Privacy Settings in Facebook<sup>TM</sup> Profiles: Evaluating the Impact of Media Context and Gender

Abstract: The present study examined disclosure and use of privacy settings in online social networking profiles as a function of the media context (i.e., online versus hard copy (paper-and-pencil) Facebook TM profiles). Gender was also examined. Overall, participants disclosed more information when constructing a profile for another person when using a hard copy paper-and-pencil format than an online context. Gender differences were not uniform across media contexts, however, in contrast to traditional disclosure theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Additionally, previous work that analyzed attitudes toward privacy on Twitter [93,94] solely focused on whether users set their accounts private or not, unlike our study which specifically tested for the login verification feature. Still, overall results for RQ1 did not confirm variations of privacy preferences in different SES or demographic populations observed by prior studies [24,25,92,93]. For self-disclosure, our findings suggest that participants' gender and education level statistically affect their information sharing behaviors on Twitter.…”
Section: Socio-demographics and Privacy Behaviorscontrasting
confidence: 94%
See 2 more Smart Citations
“…Additionally, previous work that analyzed attitudes toward privacy on Twitter [93,94] solely focused on whether users set their accounts private or not, unlike our study which specifically tested for the login verification feature. Still, overall results for RQ1 did not confirm variations of privacy preferences in different SES or demographic populations observed by prior studies [24,25,92,93]. For self-disclosure, our findings suggest that participants' gender and education level statistically affect their information sharing behaviors on Twitter.…”
Section: Socio-demographics and Privacy Behaviorscontrasting
confidence: 94%
“…Firstly, statistical analyses on the login verification feature demonstrate that a user's socioeconomic status or demographic factors have no impact on their usage of the privacy protection feature, contradicting our expectations. Previous literature showed conflicting results that gender and age indicators are related to the use of privacy enhancing tools [24,25,92]. Additionally, previous work that analyzed attitudes toward privacy on Twitter [93,94] solely focused on whether users set their accounts private or not, unlike our study which specifically tested for the login verification feature.…”
Section: Socio-demographics and Privacy Behaviorsmentioning
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, gender differences in risk taking in e-Commerce research by Bartel-Sheehan (1999), Fogel and Nehmad (2009), and Youn and Hall (2008) found that females perceived greater privacy risks online and reported higher levels of privacy concern than males. In an experimental study, Nosko et. al (2013) showed that males disclosed more personal information online while females employed more privacy settings than males.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%